2017
DOI: 10.4236/ojbm.2017.52021
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Compliance and Growth Opinions on SMEs Compliance Decisions: An Empirical Evidence from Ghana

Abstract: Generally, there has been an increase in the trend of interest of majority of people evaluating tax compliance decisions due to the fact that taxes help in funding public expenditures as well as boosting the expansion of most SME businesses. On the other hand, there has also been a sudden increase of interest in the development of Small and Medium Scale Enterprises (SMEs). In most developing and developed countries, SMEs are the spine of economic growth. Therefore, it is necessary that concentration is not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
(8 reference statements)
0
2
1
Order By: Relevance
“…The joint significant positive correlation between tax administration and SME growth contradicts the position of Atawodi and Ojeka (2012), that there is a negative relation between taxes and business growth. The positive significant impact of tax administration on SMEs' growth in this research contradicts some empirical claims (Ojeka, 2011;Mungaya, et al, 2012;Ameyaw, et al, 2016;Koranteng et al, 2017), which collectively found a negative impact of tax on SMEs' growth, but supports the position of other empirical studies (Adefeso, 2018;Tee, Boadi & Opoku, 2016).…”
Section: Discussioncontrasting
confidence: 84%
“…The joint significant positive correlation between tax administration and SME growth contradicts the position of Atawodi and Ojeka (2012), that there is a negative relation between taxes and business growth. The positive significant impact of tax administration on SMEs' growth in this research contradicts some empirical claims (Ojeka, 2011;Mungaya, et al, 2012;Ameyaw, et al, 2016;Koranteng et al, 2017), which collectively found a negative impact of tax on SMEs' growth, but supports the position of other empirical studies (Adefeso, 2018;Tee, Boadi & Opoku, 2016).…”
Section: Discussioncontrasting
confidence: 84%
“…Siyanbola et al (2017) use data from sub-Saharan Africa to show that tax policy variables such as distorting taxes have a negative but insignificant effect on economic growth, while non-distorting taxes have a positive but insignificant effect on the economic growth rate. Koranteng et al(2017) analyze the relationship between entrepreneurs' subjective views, business growth, tax collection, and tax compliance in Ghana. Using primary data from a survey of 840 registered SMEs in the (then) 10 regions of Ghana, the authors show that SMEs have negative subjective views on their growth, which negatively affects their overall tax perception and compliance with established tax norms and regulations.…”
Section: Empirical Literature On the Effects Of Taxation In Promoting...mentioning
confidence: 99%
“…According to a Finscope survey (2012), Zimbabwe has 2 748 890 SMEs, which are contributing 60% to the nation's GDP, and employing 2.9 million people. Despite this, the economic crisis, environmental changes and governance complexities, are aggressively forcing the Zimbabwean government to poorly implement SME policies, resulting in a growth 'miscarriage' of SMEs (Rurinda, Mapfumo, van Wijk, Mtambanengwe, Rufino, Chikowo & Giller, 2014, Chingwaru & Jarkata,2015).Traditionally, SMEs in the agricultural sector are always on the lookout for new solutions to address their management challenges (Koranteng, Osei-Bonsu, Ameyaw , Ameyaw , Agyeman, & Dankwa, 2017).Therefore SMEs in the agrarian sector in Zimbabwe need re-engineering since their growth will ensure food security through value-addition and increased productivity (Arudchelvan, 2015).…”
mentioning
confidence: 99%